MODERN FORMS OF THREATS AFFECTING THE NATIONAL SECURITY OF CENTRAL ASIAN STATES (Global Conference on Multidisciplinary Research and Innovation, 2026)
This research explores the modern forms of threats affecting the national security of Central Asian states. It analyzes political, economic, social, and transnational security challenges, including terrorism, drug trafficking, extremism, and regional conflicts. The study emphasizes the significance of coordinated policies, regional cooperation, and strategic security measures to ensure stability and sustainable development in Central Asia. By examining contemporary security risks, the research provides insights into both internal and external factors influencing national security and proposes practical recommendations for policymakers and regional stakeholders.
Keywords: Central Asia, national security, modern threats, terrorism, extremism, drug trafficking, regional stability, security policy, transnational challenges.